MENGURANGI PERILAKU AGRESIF MELALUI LAYANAN BIMBINGAN KELOMPOK SISWA - Siburian, Swari Rap Arion (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2023)
Education basically changes student behavior by forming attitudes and habits. The expected results from the implementation of education are not only knowledge, but also attitudes, understanding, expansion of interests, appreciation of norms and skills. So overall it forms the student's personality. In the teaching and learning process in class IX-6 of Sutomo 1 Private Middle School, Medan, there are still some students with negative behavior, such as children who are easily distracted, pay attention and do not control themselves to be a little calm, talk a lot, carry out aimless actions and lack social control. This research aims to collect data that can show the effectiveness of group guidance in reducing aggressive behavior in class IX-6 students at Sutomo 1 Private Middle School Medan for the 2022/2023 academic year. person. From the research results it can be concluded that aggressive behavior can be reduced through group guidance services for class IX-6 students at Sutomo 1 Private Middle School, Medan. This is known from the results of observations in cycle I, it is known that aggressive behavior such as being easily angry, often frustrated, easily emotional and often fighting can be said to be moderate, it is known that 50% of students' aggressive behavior has decreased. Furthermore, from observation in cycle II, it was found that the aggressive behavior of students who were easily angered, often frustrated, easily emotional, and often fought could be said to have reduced, it was found that 10% of students had reduced their aggressive behavior